Social Media Regulation, Freedom of Expression, and Civic Space in Nigeria: A Study Based on Authoritarian Mass Communication Theory - Charles A. Obiora; Amobi Peter Chiamogu; Uchechukwu Peacesonia Chiamogu (Journal of Government and Political Issues, 2022)
This study investigates the impact of the digital revolution on freedom of expression and civic space in Nigeria, particularly examining the role of social media regulation in the country's shift towards autocratization. Employing secondary data sources, the research focuses on key variables, including the government's approach to online content regulation, social media shutdowns, and capacity to regulate online content. The analysis reveals that the government's attempts to control the new media space go beyond silencing the press to outright repression, leading Nigeria towards authoritarianism characterized by reactionary tendencies. Moreover, the study finds that the combination of excessive social media regulation, a suppressed judiciary, and a weakened legislature may result in authoritarian rule in Nigeria. The paper concludes that disobedience to court orders and the use of state institutions against political opposition contribute to the erosion of democracy, highlighting the importance of a balanced approach to social media regulation to protect freedom of expression and maintain a democratic society.